Rancangan Modul Self Care sebagai Sarana Pendidikan Kesehatan terhadap Penanganan Dysmenorrhea pada Remaja - Rosmiyanti, Yanti; Suryati, Yayat; Maryati, Ida; Lismayanti, Desty; Nurhasanah, Rika (Journal of Telenursing (JOTING), 2024)
This study aims to design a self-care module for handling dysmenorrhea based on the needs of female adolescents. The method used is a qualitative descriptive exploration with a research & development model. The results of the study indicate that female adolescents' understanding of dysmenorrhea can be seen from four themes, namely perceptions about the meaning of dysmenorrhea, perceptions about the causes of dysmenorrhea, perceptions about the impact of dysmenorrhea, and perceptions about handling dysmenorrhea. In conclusion, female adolescents need educational media to hold the dysmenorrhea they experience, so this study produces a product design in the form of a dysmenorrhea handling module for schools and female adolescents. Keywords: Dysmenorrhea, Self Care Module, Adolescents